Spread (2014), volume 4 ebook Outside. - Jordan, Justin (Spread (2014), 2018)
Ravello, gifted with terrible new abilities by the Spread, has returned to, organize the raiders of the Quarantine Zone into something the world has never seen. No and company are pushed to the limit in the penultimate volume of the SPREAD saga. Collects SPREAD #18-21.. Author: Justin Jordan. Illustrator: John Bivens, Felipe Sobreiro . 2017 Justin Jordan and Kyle Strahm.